A imprescritibilidade da ação de ressarcimento ao erário fundada na prática de ato doloso de improbidade administrativa: uma análise do re 852.475/SP - Matos, Ítalo Gonçalves (Universidade Federal Rural do Semi-Árido, 2019)
This article aims to analyze the decision issued by the Brazilian Federal Supreme Court within the scope of RE 852.475 / SP, which standardized the jurisprudence about the imprescriptibility of the claims of compensation to the public treasury against intentional acts of administrative improbity. The work was developed in three topics, using the bibliographical, jurisprudential and legislative analysis, as well as the inductive method for the development of the theme. The first topic, whose character is expository, deals with the decision of the Court and the grounds expressed by the ministers. Then, an analysis of the constitutional system, of the principles concerning the subject, as well as the mechanisms of protection against probity was made. Lastly, the action of improbity and the action of reimbursement to the public treasury in the light of the system of collective tutelage is examined. Thus, the paper proposes a reflection on the limits of the State's performance in the recovery of public funds, concluding that the imprescriptibility of the claim for reimbursement of public coffers against of individuals who act with wilful misconduct to the detriment of the community is in line with the republican form without detracting from legal certainty.
Artigo acadêmico
Keywords: Improbidade administrativa; Ressarcimento; Imprescritibilidade; Administrative improbity; Refund; Imprescriptibility; CIENCIAS SOCIAIS APLICADAS::DIREITO